Assessing The Effect Of Commodity Price Shocks In The Macroeconomic Performance And Fiscal Outcomes In Latin America Countries - Páez Vallejo, Luis Alberto (2017)
In this study we investigate the role of commodity price shocks in the macroeconomic performance and in fiscal outcomes in eight Latin American (LA) economies during the period 1998-2014. Particularly, we assess the role of the commodity cycles in driving the business cycle in LA economies and how it influences also the adjustment of the fiscal policy. To do it, we constructed a specific commodity index for each country based in Medina methodology (2010). To exploit this relationship,we analyzed the effect of index commodity prices shocks using a Panel Vector Auto Regression methodology (PVAR) and using the Cholesky identification. The macroeconomic effects and fiscal reactions of LA countries are compared with a set of high income commodity exporting countries. The results of the PVAR methodology indicate that commodity cycles is a potential cause of economic cycles in LA countries, and that the magnitude of the effect is more important inLA countries compared to high income commodity countries. In the same line, evaluating the direct effect of the commodity shock in primary expenditure, we found that in LA countries the fiscal policy is procyclical while high income commodity countries, despite having a significant impact on their fiscal incomeswindfall revenues, they show a counter cyclical fiscal policy. This result supports the idea that the fiscal policy in LA countries can be a potential factor that can amplify the transmission mechanism of the inherent volatility of commodity prices to macroeconomic aggregates.